2015
DOI: 10.5752/p.1984-6606.2015v15n41p5
|View full text |Cite
|
Sign up to set email alerts
|

Relações De Interdependência Entre Confiança, Comprometimento, Qualidade Percebida E Lealdade Em Estudantes Do Ensino Superior

Abstract: <p>A competitividade dos mercados, inclusive do mercado de ensino superior, tem forçado as organizações, neste caso as instituições de ensino superior, a melhorar a gestão da relação com seus clientes ou estudantes. Assim, o tema lealdade torna-se um estudo de extrema importância, inclusive no campo do ensino superior, o qual tem demonstrado um grande dinamismo, tanto pelo crescimento da demanda como pelo crescimento da oferta, aquecendo a competição principalmente junto às instituições privadas. Desta f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 48 publications
(33 reference statements)
0
7
0
6
Order By: Relevance
“…Studies have found a strong link between the constructs 'perceived quality' and 'repurchase intention.' The literature points out that perceived quality can generate customers' commitment, loyalty, value perception, satisfaction, repurchase intention, positive word-of-mouth communication, besides enhancing profitability and reducing organization costs (Basso, Schwab, Pólvora, Marques, Pereira, & Slongo, 2008;Hennig-Thurau et al, 2001;Zeithaml, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found a strong link between the constructs 'perceived quality' and 'repurchase intention.' The literature points out that perceived quality can generate customers' commitment, loyalty, value perception, satisfaction, repurchase intention, positive word-of-mouth communication, besides enhancing profitability and reducing organization costs (Basso, Schwab, Pólvora, Marques, Pereira, & Slongo, 2008;Hennig-Thurau et al, 2001;Zeithaml, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they tend to repurchase regardless of specific prices (Low, Lee, & Cheng, 2013). According to Berry (1983), trust is shown from the moment the company presents its clients with open channels for communication, guarantees of the service provided, and a high standard of conduct. Trust provides a guarantee of a consistent and competent company's performance, ensuring that consumers continue to gain value in future business from the same supplier (Sirdeshmukh et al, 2002).…”
Section: Trust and Repurchase Intentionmentioning
confidence: 99%
“…In the last decades, studies related to customer loyalty have contributed to the literature in several aspects and markets including the loyalty/retention view of college students (Anjos Neto, 2003;Basso et al, 2015;Bergamo et al, 2011;Hennig-Thurau et al, 2001). Most of them use Hennig-Thurau et al's model, which integrates a quality model of the relationship with Tinto's model (1975) and emphasizes aspects of the student including academic and social integration that can influence the commitment to HEIs (Tinto, 1975, 1993, as cited in Vasconcelos et al, 2009.…”
Section: Academic and Social Integrationmentioning
confidence: 99%
“…In the use of a channel based on technological artifacts, confidence in the brand is crucial to minimize uncertainties of the future, especially when the individual has no control or has an incomplete control over the results (KIM; FERRIN; RAO, 2008). In addition, confidence is related to the generation of emotional involvement and customer loyalty to the company (BASSO et al, 2015).…”
Section: Customer Confidence In the Brandmentioning
confidence: 99%